Aerial tree biomass and nutrient status of soil in Acacia lenticularis (L.) Willd plantations in relation to stand density - Das, D.K.; Chaturvedi, O.P.; Laik, R.; Jha, R.K.; Chakraborty, A.K. (Indian Journal of Agroforestry, 2020)
Acacia lenticularis (L.) Willd is a leguminous tree species growing primarily in the calciorthent soil of Bihar. This study describes the above ground biomass (AGB), net primary production (NPP) and the associated changes in soil properties in eleven-year-old Acacia lenticularis (L.) Willd plantations managed at a spacing of 2 x 2 m [D1 (2500 trees ha-1)], 2 x 3 m [D2 (1666 trees ha-1)], 2 x 4 m [D3 (1250 trees ha-1)], 2 x 5 m [D4 (1000 trees ha-1)], 2 x 6 m [D5 (833 trees ha-1)], 2 x 7 m [D6 (714 trees ha-1)] and 2 x 8 m [D7 (625 trees ha-1)] in calcareous soils of north-west alluvial plain of Bihar. Height, diameter at breast height (DBH) and crown spread increased with the decrease in plant density and varied from 14.92 to 17.05 m, 15.50 to 21.44 cm and 1.80 to 3.85 m, respectively. However, AGB and NPP on per hectare basis showed reverse relationship with the density of the plantation and ranged from 34.5 to 68.3 Mg ha-1 and 3.14 to 6.22 Mg ha-1, respectively. The percent contribution of stem, branch and foliage to the total AGB ranged from 64-70%, 22-26% and 9-11%, respectively. The plant density significantly affected the electrical conductivity (EC), organic carbon (OC), and available macronutrients (N, P2O5 and K2O) showing their maximum values under density D1 and minimum under density D7. This study clearly suggests that the biomass production and soil fertility can be substantially increased by planting A. lenticularis at 2 x 2 m spacing.